Estudio de la segmentación postcefálica en el trilobites Protoryctocephalus arcticus Geyer & Peel, 2011 de la serie 2 del Cámbrico, Sur de China (2020)
In southern China, the Tsinghsutung Formation belonging to the Cambrian Series 2 outcrops in the Balang region. Contemplate a wide variety of organisms including Protoryctocephalus articus. For this study, 294 specimens in excellent preservation conditions were considered to analyse the ontogeny of these organisms, to obtain the trunk development scheme. For this, an exhaustive count of thoracic segments, pygidium segments and total length of each organism was made. Eight grades were found in the meraspid phase from G8 to G15, as well as growth patterns, but they are already described for other trilobites. Per the models proposed by Hughes et al. and Minelli et al. the growth models that best matched P. articus were established. In addition, alternation was found between the anamorphic phase where the thoracic segments increase and the epimorphic phase where they remain constant, despite the tendency to increase, there is no relationship between the number of...